Creating a Community School Museum: Theory into Practice. Issue 1 (1st December 2001) - Kerrigan, Sonia
This case study investigates the educational purposes and benefits of creating a school museum for primary schoolchildren. It identifies how such a museum might help in the wider education of pupils, the teaching of the English statutory national curriculum for history and other subjects. The paper analyses the process by which a middle school set up it's own school museum designed to operate authentically as a real community museum involving not just the children attending the school but also the local community. The project passed through four phases: initiation, planning, establishment and running. In the context of bringing about change certain factors were crucial: the support of the head teacher and senor management, a specific set of needs that such a museum might meet, staff, pupil and community support, expert external support and guidance and the physical resources to implement the vision. To create an authentic museum guidance was sought from local museums, the Education Officers working within them and others involved museum management.